INFRASTRUCTURE DEVELOPMENT AND PEACEBUILDING IN PAPUA: EXAMINING THE ROLE OF SDGS 9 AND 16 - Ahmanto, Darin Nafisa Mayumi Puri; Wibiksono, Almirah Nahda Ayu; Jariah, Nandratul; Halimatussaddiah, Nabila Tenri (BHUVANA: Journal of Global Studies, 2026)
This study aims to analyze the role of infrastructure development in supporting the peacebuilding process in Papua, with reference to Sustainable Development Goals (SDG) 9 and SDG 16. Infrastructure development is strategically important for fostering sustainable peace, as the issues in Papua are not only related to security but are also influenced by development disparities, structural poverty, limited access to basic services, and the marginalization of indigenous communities. This study employs a descriptive qualitative method, utilizing a literature review and secondary data analysis. Johan Galtung’s theoretical framework of peacebuilding is used to understand the relationship between infrastructure development and the concept of positive peace. Research findings indicate that infrastructure development have contributed to improved regional connectivity and economic activity among local communities. However, the impact has not yet translated into corresponding improvements in the well-being and social cohesion of Papuan communities. Therefore, the integration of SDGs 9 and 16 is essential to ensure that infrastructure development is not solely focused on economic growth, but also strengthens social justice, inclusive governance, and trust in state institutions as the foundation for sustainable peacebuilding.